2018
DOI: 10.1038/nature25507
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic origins due to short G1 phases underlie oncogene-induced DNA replication stress

Abstract: Oncogene-induced DNA replication stress contributes critically to the genomic instability present in cancer1–4. However, elucidating how oncogenes deregulate DNA replication has been impeded by the difficulty in mapping replication initiation sites on the human genome. In this study, using a sensitive assay to monitor nascent DNA synthesis in early S phase, we identified thousands of replication initiation sites in cells before and after induction of the oncogenes CCNE1 or MYC. Remarkably, both oncogenes induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
373
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(394 citation statements)
references
References 31 publications
(42 reference statements)
19
373
0
2
Order By: Relevance
“…Analysis of the consequences of drug‐mediated inhibition of transcription strongly suggested that a short G1 phase reduces the window of time during which ongoing transcription can clear the gene bodies of pre‐RC prior to replication initiation. The authors proposed that activation of intragenic origins induces conflicts between transcription and replication, which triggers the instability observed in these early regions . Together, these reports show that transcription shapes the initiation profile in both early and late replicating domains.…”
Section: Impact Of the Replication Dynamics On Cfs Stabilitymentioning
confidence: 95%
See 1 more Smart Citation
“…Analysis of the consequences of drug‐mediated inhibition of transcription strongly suggested that a short G1 phase reduces the window of time during which ongoing transcription can clear the gene bodies of pre‐RC prior to replication initiation. The authors proposed that activation of intragenic origins induces conflicts between transcription and replication, which triggers the instability observed in these early regions . Together, these reports show that transcription shapes the initiation profile in both early and late replicating domains.…”
Section: Impact Of the Replication Dynamics On Cfs Stabilitymentioning
confidence: 95%
“…However, if the same mechanism operates at ERFSs and at CFSs, it remains to explain why, as discussed above, late replication is mandatory for CFS instability and why metaphase breaks map in the core of large transcribed fragile genes rather than in their 5′ and 3′ regions where initiation events also cluster. In addition, it would be interesting to determine how oncogene‐induced fragile regions mapped by Macheret and Halazonetis in early replicating domains relate to ERFSs. Further work will therefore be needed to reconcile the different sets of data, notably to clearly determine the role played by sequence‐dependent formation of secondary structures versus distribution of initiation events in fragile site setting.…”
Section: Impact Of the Replication Dynamics On Cfs Stabilitymentioning
confidence: 99%
“…Cyclin E overexpression was shown to induce the occurrence of conflicts between the replication and transcription machineries due to increased numbers of simultaneously active replication forks . In a recent study, it was further shown that cyclin E overexpression and Myc activation induced a novel set of DNA replication origins that mapped within highly transcribed genes . These ectopic origins are normally suppressed by transcription during G1, but premature S‐phase entry, before all genes had been transcribed, allowed firing of origins within genes in cells with activated oncogenes.…”
Section: Factors Leading To Dna Replication Stressmentioning
confidence: 99%
“…Origin usage following oncogene activation was recently investigated genome-wide. The authors found that in these conditions new initiation zones, which were normally suppressed by transcription in G 1 , appear in intragenic regions 47 . These results also confirm an observation in drosophila showing that active transcription modulates MCM2-7 distribution 48 .…”
Section: Coordination Between Replication Origin Licensing and G 1 Lementioning
confidence: 98%